Cytokine-induced acute inflammation in the brain and spinal cord. - Schnell, L; Fearn, S; Schwab, M; Perry, V; Anthony, D (1999)
Different compartments in the central nervous system mount distinct inflammatory responses. The meninges and choroid plexus respond to pro-inflammatory stimuli in a manner reminiscent of a peripheral inflammatory response, whereas the brain parenchyma is refractory. Trauma-induced lesions in brain and in spinal cord are associated with leukocyte infiltration, blood-brain barrier (BBB) breakdown, and secondary tissue destruction. Unexpectedly, these phenomena are generally more pronounced in the parenchyma of the spinal cord than in the parenchyma of the brain. To investigate whether these differences between brain and spinal cord can be attributed, at least in part, to differing sensitivities to proinflammatory cytokines, we stereotactically injected recombinant rat (rr) TNFalpha or rrIL-1beta into the striatum or the spinal cord of Wistar rats. In the brain, the injection of rrTNFalpha failed to evoke BBB breakdown or leukocyte recruitment, whereas in the spinal cord injection of TNFalpha resulted in marked BBB breakdown and leukocyte recruitment. Similarly, the injection of rrIL-1beta into the brain parenchyma failed to induce BBB breakdown and gave rise to only minimal neutrophil recruitment, whereas the injection of rrIL-1beta into the spinal cord induced significant BBB breakdown and recruitment of neutrophils and lymphocytes. Thus, using a minimally invasive injection technique, equivalent in both circumstances, we have shown that there are marked differences in the inflammatory response between the brain parenchyma and spinal cord parenchyma. This observation has important implications for the treatment of spinal cord injuries.